Cognitive Behavioral Therapy plus Amitriptyline for Children and Adolescents with Chronic Migraine Reduces Headache Days to ≤4 Per Month. Issue 4 (18th March 2016) - Kroner, John W.; Hershey, Andrew D.; Kashikar‐Zuck, Susmita M.; LeCates, Susan L.; Allen, Janelle R.; Slater, Shalonda K.; Zafar, Marium; Kabbouche, Marielle A.; O'Brien, Hope L.; Shenk, Chad E.; Rausch, Joseph R.; Kroon Van Diest, Ashley M.; et al.
Abstract : Objective: The objective of this secondary analysis of results from a previously published trial (Clinical Trials Registration Number: NCT00389038 ) in chronic migraine in children and adolescents was to examine if participants who received cognitive behavioral therapy and amitriptyline reached a greater level of reduction in headache frequency that no longer indicated a recommendation for preventive treatment as compared to those who received headache education and amitriptyline. Background: Chronic migraine negatively affects children's home, school, and social activities. Preventive medication therapy is suggested for 5 or more headaches per month. Reduction to one headache day per week or less may suggest that preventive treatment is no longer indicated and provide a clinically relevant outcome for treatment efficacy and patient care. Methods: Randomized study participants ( N = 135) kept a daily record of their headache frequency during 20 weeks of treatment and during a 1 year follow‐up period. Baseline headache frequency was determined at the end of a 28 day screening period. Post treatment frequency was determined at 20 weeks ( N = 128 completed) and post treatment follow‐up was measured 12 months later ( N = 124 completed). A chi‐square test of independence was conducted by treatment group and by time point to determine group differences in the proportion of headache days experienced. Results: At 20 weeks (post treatment), 47% of the cognitive behavioral therapy plus amitriptyline group had ≤4 headache days per month compared to 20% of the headache education plus amitriptyline group, ( P = .0011), and 32% of the cognitive behavioral therapy plus amitriptyline group had ≤3 headache days per month at 20 weeks compared to 16% of the headache education plus amitriptyline group, ( P = .0304). At the month 12 follow‐up, 72% of the cognitive behavioral therapy plus amitriptyline group had ≤4 headache days per month compared to 52% of the headache education plus amitriptyline group, ( P = .0249), and 61% of the cognitive behavioral therapy plus amitriptyline group had ≤3 headache days per month at their month 12 follow‐up compared to 40% of the headache education plus amitriptyline group, ( P = .0192). Conclusions: Participants who received cognitive behavioral therapy and amitriptyline were more likely than participants who received headache education plus amitriptyline to reach the clinically meaningful outcome of less than or equal to 4 headache days per month at both time points. These results may help inform what treatment outcomes are possible for children and adolescents suffering from chronic migraine and provides further evidence for behavioral treatment to be considered as a key part of a first line treatment regimen.